Humanization through Contemplation A Critique and Review on the Book Thought and Thinking - Reza Nasiri Hamed (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The contemporary identity of Iranians in relation to their past as well as their interaction with global relations and at the same time its connection with development, has been the subject of various discussions among thinkers. In the book Thought and Thinking, "Farhang Rajaei" inspired by the "The Law of World Governance Reason" in Letter of Tansar as a theoretical basis and equivalent to the principles of political science in the current world, has addressed reflections of thinkers from Iran and the world. His main concern is the pathology of the current situation governing the intellectual relations of Iranians and providing a way to play an active role in relations between countries so that they can achieve what is called playing in politics. To this end, he uses the past intellectual heritage try to suggest a link between thought and action that serves humanization and, in a sense in a dynamic and, of course, the endless process in which, in his opinion, even the so-called developed world countries are in the middle of that. The present paper, while reflecting on the above work, discusses some of the questions that arise from the author's concerns. However, the author's commendable effort in terms of the possibility of compatibility between the various components of the idea also has some points that will be mentioned.